2014
DOI: 10.1016/j.rmed.2014.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Nasal and systemic inflammatory profile after short term smoking cessation

Abstract: The short term smoking abstinence decreased systemic inflammation and improved nasal mucociliary clearance, despite not having changed the nasal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 60 publications
0
19
0
1
Order By: Relevance
“…On the one hand, it will eliminate the anorectic effect of tobacco, improving diet quality (223). On the other, systemic inflammation and oxidative stress, as well as protein synthesis/breakdown imbalance will be reduced, with improvements in body weight, as well as in muscle mass and function (224)(225)(226)(227).…”
Section: Avoid Tobacco Smokingmentioning
confidence: 99%
“…On the one hand, it will eliminate the anorectic effect of tobacco, improving diet quality (223). On the other, systemic inflammation and oxidative stress, as well as protein synthesis/breakdown imbalance will be reduced, with improvements in body weight, as well as in muscle mass and function (224)(225)(226)(227).…”
Section: Avoid Tobacco Smokingmentioning
confidence: 99%
“…Mendal et al [46] reported that serum IL-6 levels were increased in smokers. However, Rodrigues et al [21] found that quitters and active smokers had similar IL-6, IL-8, and IL-10 levels, and they mentioned that 30 days was a relatively short period for quitting. Similarly, Van Keulen et al [47] found in their study in Brazil that serum levels of TNF-α, IL-1, IL-6, IL-8, IL-10 and IL-12 were similar at 4 th month of quitting when compared to basal levels.…”
Section: Discussionmentioning
confidence: 99%
“…In the same study, IL-1a and TNF-α levels were found to be decreased to basal levels at 8 weeks after the elimination of the smoke. Rodrigues et al [21] conducted a study in Brazil with 25 patients, and found that TNF-α levels decreased significantly in patients who quit smoking for 30 days when compared to active smokers. In our study, we found that serum TNF-αlevels were decreased significantly at 2 months after quitting when compared with the basal levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…42,43 Reduction of inflammatory markers in blood after cessation of smoking for a period of one month shown by a recent study also suggest the role of smoking on systemic inflammation. 44 Increased Nitric oxide bioavailability is reduced and endothelium dependent vasodilation is decreased as a results of cigarette smoking. 45,46 Activity and expression of the enzyme endothelial nitric oxide synthase is altered by cigarette smoke.…”
Section: Oxidative Stress and Inflammatory Markersmentioning
confidence: 99%